Fire Influence on the Ants Community in Savanic and Forest Environments of the Cerrado Biome - Costa,Aline das Graças (2022)
Abstract The objective of this work is to evaluate the effect of fire on ant assemblages in savanna and forest typologies in the Reserva Natural da Serra do Tombador in Cavalcante - Goiás, Brazil. Ant pitfalls traps were installed and subdivided into Burnt Cerrado (BC), Unburnt Cerrado (UC), Burnt Forest (BF) and Unburnt Forest (UF), and the samples were sorted, assembled and identified. The constancy and abundance of individuals, and the frequency of distribution of the genera in the total area and by treatment were evaluated. The UF, BF, UC and BC had 19, 14, 8 and 15 genera, with Jackknife 1 index indicating 18.5, 24.4, 8.9 and 20.4 respectively. The Shannon diversity index for the genera was 0.8462, 0.7604, 0.6448 and 0.5992 for UF, BF, BC and UC respectively. The Cerrado showed greater abundance of individuals and greater ant diversity index in relation to Forest when in presence of fire.